2014
DOI: 10.5897/jen2014.0100
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility test of female anopheles mosquitoes to ten insecticides for indoor residual spraying (IRS) baseline data collection in Northeastern Nigeria

Abstract: Malaria is a major public health problem in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
20
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 22 publications
9
20
1
Order By: Relevance
“…from the evaluated LGAs of Lagos State. Several previous studies in different parts of Nigeria have recorded similar resistant level to different Pyrethriods and DDT 7,9,11,12 . Pyrethriods resistance recorded in these study areas could be detrimental to the effectiveness of LLINs as they are the only class of insecticide currently approved for use in LLINs.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…from the evaluated LGAs of Lagos State. Several previous studies in different parts of Nigeria have recorded similar resistant level to different Pyrethriods and DDT 7,9,11,12 . Pyrethriods resistance recorded in these study areas could be detrimental to the effectiveness of LLINs as they are the only class of insecticide currently approved for use in LLINs.…”
Section: Discussionmentioning
confidence: 70%
“…The effectiveness and efficacy of the few insecticides approved for the control of malaria vectors by WHO has been greatly hampered by the advent of insecticide resistance. In Nigeria, Pyrethriods and DDT resistance has been reported in several parts of the country [7][8][9][10][11][12] . Insecticides resistance in malaria vectors can result from one or combination of behavioral changes, morphological modifications, target site mutation and metabolism by detoxifying enzymes.…”
mentioning
confidence: 99%
“…The paucity of information on dominant vector species (DVS) is most extreme in the Sahelo-Sudanian region of the country. With the exception of few focal studies 7,8 reliable information on the DVS from northern Nigeria is grossly lacking for decades following the comprehensive study conducted in Garki 9 . This is in stark contrast to the situation in southern part of Nigeria (especially the south-west), where significant progress on malaria vector bionomics has been achieved 1013 .…”
Section: Introductionmentioning
confidence: 99%
“…This implies that these pyrethriod treated nets have been in use till date in these areas. Previous studies revealed that use of LLINs could result in development of insecticide resistance in Anopheles mosquitoes to pyrethriods [9,23]. The possibility of these LLINs inducing changes in the adult mosquito populations thus contributing to the resistance status recorded in these study areas may not be ruled out.…”
Section: Discussionmentioning
confidence: 90%